Fighting The Plague For Fate Of The World In DominicSena's Season Of The Witch Movie (2011): A Sociological Approach - Fatiningsih, Wazir Avi, Drs. Abdillah Nugroho, M.Hum, Drs. Sigit Haryanto, M.Hum (2013)
The problem of the study is how fighting the plague for fate of the world reflected in Season of the Witch movie. The objectives of the study are to analyze Season of the Witch (2011) movie based on the structural elements of the movie and to describe the fighting plague of the world in Season of the Witch (2011) movie based on the sociological approach. This study belongs to qualitative research. In this research, there are two types of data source, namely primary and secondary data source. The primary data source is the movie itself, meanwhile the secondary data source is any literature related with the study. The researcher collects the data from both, primary and secondary data source in a short of document as evidence. The study uses library research of descriptive analysis. Based on the analysis the researcher draws some conclusions as follows: firstly, based on the structural analysis of each element, it shows that the character and characterization, plot, style, theme and point of view are related to each other and form a solid unity. Secondly, based on sociological analysis, the researcher concludes that how to create world peace needed a sacrifices even tough until the lost live it can be seen from the main character of the movie when fight with demon to end the terrible black plague.